Relationship between youths’ attitudes and beliefs towards violence in foreign movies - Ahmad Ghazali, Akmar Hayati; Munusamy, Kalaivani (Human Resource Management Academic Research Society, 2020)
Violence in movie is one of the specific learning conditions believed to be a potential contributor towards the growth of violent behaviour among youths. The purpose of this paper is to examine the relationship between exposure of violent scenes in foreign movies and the violent behavior among Indian youths. A quantitative study involved 400 Indian youths aged between 15 to 19 years old. To select the respondents, a convenient sampling was performed. The data was analyzed using SPSS. The results show that Indian youths who watch Tamil movie more than 4 hours per day would be more influenced with the exposure of violence and it is associated with the increase in violent behaviour. It can be concluded that there is a positive connection between violence in Tamil movie on attitudes, beliefs and violent behaviour. Findings from this study can be used to explore a more effective way such as increasing control from parents to overcome violent behaviour among youths. Film Censorship Board (LPF) has to filter and ban the screening of violent movies. Thus, it could prevent and can help in combating screening of violent actions movies and future research.